Antibiotic prescribing in UK out- of- hours primary care services: a realist- informed scoping review of training and guidelines for healthcare professionals. Issue 3 (June 2021) - Alves, Paula Gomes; Hayward, Gail; Leydon, Geraldine; Barnes, Rebecca; Woods, Catherine; Webb, Joseph; Booker, Matthew; Ireton, Helen; Latter, Sue; Little, Paul; Moore, Michael; Nicholls, Clare-Louise; et al.
No abstract available